Bacterial and Fungal Keratitis: A Retrospective Analysis at a University Hospital in Switzerland - Bograd, Alexandra; Seiler, Theo; Droz, Sara; Zimmerli, Stefan; Früh, Beatrice; Tappeiner, Christoph (Klinische Monatsblätter für Augenheilkunde, 2019)
Background Infectious keratitis is a serious corneal disease and may lead to permanent visual deterioration if not treated rapidly and effectively. In order to determine possible changes in the spectrum of pathogens over time, we evaluated the pathogenic organisms of keratitis at a university hospital in Switzerland, comparing two time periods within a decade.Methods In this retrospective study, 417 patients with the clinical diagnosis of bacterial or fungal keratitis in 2006/07 and 2015/16 were enrolled. In an additional analysis, all cases of fungal keratitis between 2006 and 2016 were evaluated. Collected parameters were age, gender, side, use of contact lenses, systemic, neurological and ocular diseases, trauma, previous surgery, and systemic and topical therapy before presentation. In each patient, microbiological results of corneal smears such as growth and antibiotic resistance were analysed.Results A total of 163 and 254 eyes were included in 2006/07 and 2015/16, respectively. In 2006/07, a culture of smears revealed a bacterial cause in 70 eyes (42.9%) and a fungal cause in 4 eyes (2.5%), whereas in 2015/16, bacterial growth was found in 115 eyes (45.3%) and fungal growth in 6 eyes (2.4%). The most common bacteria in 2006/07 and 2015/16 were coagulase-negative Staphylococci (44.3 vs. 49.6%), Pseudomonas aeruginosa (18.6 vs. 13.9%), Staphylococcus aureus (10 vs. 16.5%), Corynebacterium spp. (8.6 vs. 5.2%), and Moraxella spp. (7.1 vs. 9.6%). Candida parapsilosis was the most common fungal isolate in both groups (25 vs. 33.3%). Between 2006 and 2016, fungal keratitis was found in 37 eyes (Candida spp. n = 11, Fusarium spp. n = 11, Aspergillus spp. n = 5, others n = 10). All patients with Fusarium spp. keratitis had a history of wearing contact lenses.Conclusion The most commonly isolated bacterial organisms were Staphylococci and Pseudomonas spp., whereas fungal keratitis was mainly due to Candida spp. or Fusarium spp. No relevant variation in causative pathogens was observed between the two time periods.
Keywords: bacterial keratitis; fungal keratitis; microbiology; coagulase-negative Staphylococcus; Pseudomonas aeruginosa